The Effectiveness of the Waste Reporting Incentive Program in Supporting Community-Based Waste Management in Padang City - Aviva Amalda; Lince Magriasti (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze the effectiveness of the Waste Reporting Incentive Program in supporting community-based waste management in Padang City as regulated in Padang Mayor Regulation Number 3 of 2021. The research employs a descriptive qualitative method focusing on three dimensions of effectiveness according to Duncan (1973): goal attainment, integration, and adaptation. Data were collected through in-depth interviews, documentation studies, and observations at the Padang City Environmental Agency. The results show that this program has not been effective across all measured dimensions. In the goal attainment dimension, out of 84 reports received during 2022-2025, only 8.4% were valid, and no incentives were successfully disbursed, while waste volume actually reached its highest peak in 2025 (669 tons/day). In the integration dimension, internal inconsistencies and low outreach coverage were found, causing the majority of the public to be unaware of this program. In the adaptation dimension, although regulations have been adjusted twice, the program has not adapted to budget constraints (IDR 1,000,000/year), geographical participation disparities, and the complexity of reporting requirements. The main obstacles include resource limitations, weak internal coordination, low public trust, and potential program misuse. This study recommends budget adjustments, simplification of reporting mechanisms, strengthening community-based socialization, and continuous evaluation to improve program effectiveness.